Impact of environmental awareness level to water quality status in Kenyir Lake, Malaysia - Mohd Khairul Amri, Kamarudin; Mohamad Hazanur, Syahfiq Hasbullah; Mohd Armi, Abu Samah (2020)
Environmental awareness is very important to ensure the water quality status and ecosystem sustainability in a river basin. The purposes of the study are to determine the extent of knowledge and education level are closely related to the environmental awareness level among local communities and its effect on the water quality status. The quantitative method has been used through questionnaire.The respondents were selected based on Krejcie and Morgan sample size method. This study was analysed the data using Discriminant Analysis, Hypothesis Testing (two sample t-test and z-test) and Descriptive Analysis to find the mean value and p-value. Based on the result, the various factors of pollution not only focus on local communities but also involve outsiders such as tourists and anthropogenic factors such as logging, deforestation and waste disposal. All 10 questions were analysed and found the p-value >0.05.These results show no significant difference between the Male and Female respondents of the level of awareness in Kenyir Lake communities about water quality status. The water quality status recorded as Class I and II according to National Water Quality Standards. The Kenyir Lake's water resources do not require treatment and are categorized as safe for both humans and animals.